Are Scrapbooks Able to Increase Tsunami Disaster Literacy? An Analytical Study of Junior High School Students Materials - Kiki Septaria; Atika Fatharani; Ahmad Baihaqi (SEJ (Science Education Journal), 2025)
Tsunami disaster mitigation is a crucial aspect of enhancing community preparedness, particularly among junior high school students in tsunami-prone areas. However, students' disaster literacy remains low due to the lack of engaging and interactive learning media. This study aims to develop and evaluate the effectiveness of Scrapbook-based learning media in improving students’ tsunami disaster literacy. Using a Research and Development (R&D) approach, this study follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) and employs a mixed-method approach combining quantitative and qualitative methods. The research involved four expert validators (material, media, language, and disaster mitigation practitioners) and 65 students from Al-Amin Junior High School, with an initial trial conducted on 15 students. The validation results indicate that the developed Scrapbook media is valid, with an average assessment score of 84%. The paired sample t-test revealed a significant improvement in students' disaster literacy, with a significance value of 0.000 < 0.005. These findings demonstrate that Scrapbook media effectively enhances students' understanding of tsunami disaster mitigation. The implications of this study highlight the importance of integrating interactive and visually engaging learning media into disaster education curricula to foster student engagement and strengthen their preparedness for future disasters.